Per3 VNTR polymorphism and chronic heart failure - Lipkova, Jolana; Bienertova-Vasku, Julie Anna; Spinarova, Lenka; Bienert, Petr; Hlavna, Marian; Pavkova Goldbergova, Monika; Parenica, Jiri; Spinar, Jindrich; Vasku, Anna (Biomedical papers, 2014)
Aims: The aim of this study was to investigate the relationship between gene Period3 (Per3) variable number tandem repeat (VNTR) polymorphism and chronic heart failure (CHF).Methods: The study subjects (372 patients of Caucasian origin with CHF and 332 healthy controls) were genotyped for Per3 VNTR polymorphism using an allele-specific PCR.Results: No significant differences in genotype or Per3 VNTR allele frequencies were found between CHF cases and controls (Pg=0.30, Pa=0.52). No significant differences were uncovered either between CHF cases according to etiology (DCMP vs. IHD; Pg=0.87, Pa=0.91). In the multivariate regression modeling, no predictive function of VNTR Per3 polymorphism on ejection fraction or NYHA class, hyperlipidaemia or type II diabetes risk was found.Conclusion: Per3 VNTR polymorphism is not a major risk factor for chronic heart failure or a factor modulating the severity of the CHF in this population.
Keywords: circadian clock; Per3; polymorphism; case-control study; chronic heart failure